KESEIMBANGAN KERJA DAN KEHIDUPAN DALAM MSDM: ANALISIS LITERATUR TERHADAP PENGARUHNYA PADA KESEJAHTERAAN KARYAWAN - Simangunsong, Ruben; Nauli, Mawar; Alfons Depari, Oyke; Nauli, Harum; Irani Br Tarigan, Miska (Penerbit Lafadz Jaya, 2025)
This study examines the impact of work-life balance (WLB) on employee well-being and employee retention with a focus on human resource management (HRM) policies. Based on a literature review from various sectors (government, private, education, and health) and various approaches (quantitative, qualitative, and mixed-method), this study finds that good WLB policies can increase job satisfaction, reduce work stress, and improve psychological well-being. In addition, effective WLB policies also contribute to higher employee retention. This study identifies several key success factors, such as managerial support, an organizational culture that supports balance, and the integration of WLB into HRM strategies. However, there are limitations in the existing literature, such as the dominance of studies from developed countries and the lack of longitudinal studies. Further research is needed to explore the long-term impact and implementation of WLB policies in the context of developing countries.